Product Non-Conformity in TikTok Shop Transactions: A Case Study of E-Commerce Buying Practices - Nur Hasanudin; Muhammad Hamdi (International Conference on Islamic Economic (ICIE), 2026)
The rapid development of technology has greatly facilitated various aspects of life, one of which is in the trade sector, which has now shifted to online platforms. One of the most widely used applications for transactions is TikTok Shop. Although it offers convenience, online shopping also brings various problems, especially regarding the quality of products that do not match the description and the discrepancy in shipping times. This results in consumer dissatisfaction, as they often face difficulties when attempting to return items. This study aims to analyze online shopping practices on TikTok Shop from the perspective of Islamic economics, particularly in terms of transaction compliance with the principles of fiqh muamalah. This research uses a descriptive qualitative approach, with data collection techniques through direct interviews with students from Universitas Al Falah Assunniyah Kencong Jember who have made transactions on TikTok Shop. The findings indicate that online transactions on TikTok Shop often do not meet the valid requirements in Islam, particularly regarding the mismatch between the delivered goods and the description, as well as the buyer’s right to return goods. Therefore, a deeper understanding of the principles of fiqh muamalah in online transactions is essential to ensure that these trade activities align with Islamic regulations. This study also emphasizes the importance of implementing systems that provide guarantees for consumers in the form of the right of khiyar (option) to continue or cancel transactions